1999
DOI: 10.1021/ja990750c
|View full text |Cite
|
Sign up to set email alerts
|

Carbon−Carbon Bond Formation Reaction of Zirconacyclopentadienes with Alkynes in the Presence of Ni(II)-complexes

Abstract: Zirconacyclopentadienes, prepared from two alkynes or a diyne, reacted with the alkyl-, trimethylsilyl-, or alkoxy-substituted third alkyne as well as an alkyne with an electron-withdrawing group in the presence of a stoichiometric amount of NiBr 2 (PPh 3 ) 2 to give benzene derivatives in good yields. Heteroatom-containing diynes such as dipropargylbenzylamine and propargyl-homopropargylbenzylamine gave isoindoline and tetrahydroisoquinoline derivatives in good to high yields. This procedure was also used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(65 citation statements)
references
References 22 publications
2
63
0
Order By: Relevance
“…Using unreactive alkynes or bulky phosphine ligands, many trigonal planar bisphosphinemonoalkyne complexes could be isolated by Pörschke, [24] for example, (Cy 3 P) 2 Ni(h 2 -C 2 H 2 ), [24] and by others, e.g., (Ph 3 P) 2 Pd-(h 2 -MeO 2 CC CCO 2 Me), [25] [h 2 -i-Pr 2 PCH 2 CH 2 P-iPr 2 ]Ni(h 2 -PhC CPh), [26] (h 2 -Cy 2 PCH 2 CH 2 PCy 2 )Ni(h 2 -PhC CPPh 2 ). [27] There are also recent preparative mechanistic studies discussing metallacyclopentadienes, e.g., with Fe as the metal center, [28] Ni, [29±31] Ti, [32,33] Zr, [34] Rh, [35±37] Ru, [38,39] lanthanides, [40] and actinides. [41] Although different types of model compounds have been synthesized, [42±44] the final step is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Using unreactive alkynes or bulky phosphine ligands, many trigonal planar bisphosphinemonoalkyne complexes could be isolated by Pörschke, [24] for example, (Cy 3 P) 2 Ni(h 2 -C 2 H 2 ), [24] and by others, e.g., (Ph 3 P) 2 Pd-(h 2 -MeO 2 CC CCO 2 Me), [25] [h 2 -i-Pr 2 PCH 2 CH 2 P-iPr 2 ]Ni(h 2 -PhC CPh), [26] (h 2 -Cy 2 PCH 2 CH 2 PCy 2 )Ni(h 2 -PhC CPPh 2 ). [27] There are also recent preparative mechanistic studies discussing metallacyclopentadienes, e.g., with Fe as the metal center, [28] Ni, [29±31] Ti, [32,33] Zr, [34] Rh, [35±37] Ru, [38,39] lanthanides, [40] and actinides. [41] Although different types of model compounds have been synthesized, [42±44] the final step is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…[10] In view of literature work on transmetalation from zirconacycles to nickel, [11] we wondered whether the resultant nickelacyclopentane generated through transmetalation from the corresponding zirconacyclopentane would be active toward alkyne insertion. Such an approach may lead to onepot synthesis of dihydrobenzocarboranes through an equivalent of a three-component [12] with one equivalent of 1-hexene or styrene in toluene heated to reflux and isolated in more than 87 % yield (Scheme 1).…”
mentioning
confidence: 99%
“…In this case no formation of the Dewar benzenes was observed, and obviously they would not be able to form because of the reaction mechanism. [8] In addition, the reaction between 2 and 3c was carried out in the presence of NiBr 2 (PBu 3 ) 2 , because it had recently been shown that the use of Ni complexes with alkylphosphanes was advantageous in certain cases. [9] Nonetheless, the biaryl 6c was formed in only 42 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…[5] However, because of selectivity problems these approaches are usually applied to cyclotrimerization of α,ω-diynes with alkynes. As for the cyclotrimerization of three alkynes to highly substituted arenes with potential atropoisomeric properties, one convenient method is based on the treatment of zirconacyclopentadienes [6] with alkynes in the presence of stoichiometric amount of CuCl, [7] NiBr 2 -(PPh 3 ) 2 , [8] or NiBr 2 (PMe 3 ) 2 . [9] This method has been successfully applied for the synthesis of polysubstituted aromatic compounds such as benzoheterocycles containing group 14 elements, [10] haloterphenyls, [11] haloterphenyls with chiral backbones, [12] perfluoroalkyl-substituted terphenyls, [13] polyacenes, [14] and ferrocenylalkynes.…”
Section: Introductionmentioning
confidence: 99%